Occurrence of Adenovirus in Fecal Samples of Wild Felids (Panthera onca and Leopardus pardalis) from Brazil: Predators as Dispersing Agents? - Machado, Ygor (2024)
Wild felids are vital to maintaining the ecological balance in natural environments as they regulate prey populations at different levels of the food chain. Changes in the dynamics of predator populations can impact the entire biodiversity of an ecosystem. There are few reports of Adenovirus infections in these animals, and little is known about their epidemiology. Therefore, a deeper understanding of these viruses within a One Health framework is essential, given their importance to animal, human, and environmental health. This study aimed to detect Adenovirus DNA in fecal samples of wild felids from a remnant of the Atlantic Forest in southeastern Brazil, renowned for its high biodiversity. A total of 43 fecal samples, 11 from jaguar (Panthera onca) and 32 from ocelot (Leopardus pardalis), were collected. The samples were subjected to viral nucleic acid extraction and genetic material amplification through PCR, followed by nucleotide sequencing. All phylogenetic analyses were based on the amino acid sequences of the DNA polymerase and IV2a genes. Adenovirus DNA was detected in the feces of both species, with two samples of each feline testing positive. This study reports, for the first time, the occurrence of Adenovirus associated with feces of Panthera onca and Leopardus pardalis. All detected sequences were grouped within the Mastadenovirus genus. Based solely on phylogenetic distance criteria, the identified sequences could be classified as Mastadenovirus bosprimum and Mastadenovirus from the vampire bat Desmodus rotundus. We hypothesize that Adenoviruses were associated with the prey consumed, which may allow the felines to act as eventual viral dispersing agents in the environment, in addition to the risk of being infected. This study provides new information on the association of Adenoviruses with wild felids and their prey, and offers important insights into the ecological dynamics of these viruses in natural environments. It suggests that wild felines may play a crucial role in viral surveillance programs.